The Effectiveness of The KUD Strategy in The Achievement of Second- Year Intermediate Students and Developing Their Inclination Towards Physics - Suleiman Al Suwaidi, Ali Salim; Abdullah Hassan, Hassan (JOM, 2023)
The aim of this research is in order to identify the effectiveness of the KUDstrategy in the academic achievement of second-grade intermediate students, andto change students' view towards physics, and the sample consisted of (83)students from the second intermediate grade in Tal Afar Intermediate School forboys for the academic year (2022-2023) for the second semester. The researcherhas chosen this school deliberately because it contains more than four divisions,as well as the cooperation of the subject teacher and the school administration inthe success of this experiment. The students were randomly divided into twogroups, the first experimental group studied strategically KUD and the secondcontrol group studied in the usual way. As well as conducting equivalences forthe two groups in (academic achievement of parents - intelligence quotient -chronological age in months - physics degree third grade intermediate - tribalinferential thinking).To achieve this goal, the researchers have prepared an achievement test, whichconsisted of (36) items, all representing a type of multiple choice and verified itsvalidity and stability as well as its psychometric properties. The second tool is themeasure of inclination towards physics, which consists in its final form of (20)paragraphs triple alternatives, and after analyzing the study data statistically usingthe T-test for two independent samples, the results showed the following:1) There is a difference y and statistical significance at the level of significance(0.05) between the average scores of the achievement test for the experimentaland control groups and in favor of the experimental group.2) There is a difference y and statistical significance at the level of significance(0.05) between the average development of the tendency towards physics forthe experimental and control groups and in favor of the experimental group